The Maillard Reaction in Food Chemistry Current Technology and Applications - Ruan, Dongliang (Chemistry of Foods,, 2018)
This book is devoted to the characterization of Maillard reaction products using mass spectrometry (MS)-based technologies. The Maillard reaction is a well-known non-enzymatic reaction between reducing sugars and proteins, and one of the most important reactions in food sciences. The authors explore different MS-based technologies to systematically investigate the Maillard reaction from amino acids, peptides and proteins. By using amino acid/peptide-sugar models, the authors also show how reactants, temperature and time affect the Maillard reaction. In this book, readers will learn more about glucosylation, and how it can improve functional properties of food proteins.